Review of small cetaceans: distribution, behaviour, migration and threats. Regional Seas reports and studies no. 177 - United Nations Environment Programme (United Nations Environment Programme, 2016)
This reference book is intended for experts in the field of marine biology, students, and conservationists as well as for interested laypersons. No comparable encyclopedia on whales has been published so far. With the exception of the sperm whale, all 72 species of toothed whales that migrate across the oceans are covered. What is new about this review is that it is based on the most recent literature available and compiled by a single author and not by a variety of experts. It highlights the threats whales are exposed to. A description and a picture are dedicated to each species. A detailed list of references to every single species adds particular value to the study. The most up to date maps available illustrate their distribution. Population size, biology, migration patterns and threats are dealt with in further chapters. These new findings on distribution, behaviour and migration will facilitate the application of targeted action plans and threat mitigating methods.